Does Current United Kingdom Childhood Cancer Research Address the James Lind Alliance Children's Cancer Priority Setting Partnership Priorities? A Grant Mapping Study - Alison Bish; Faith Gibson; Alexandra Brownsdon; Julia Chisholm; Jenny Harris; Rachel Hollis; Bob Phillips; Susie Aldiss (Health Expectations, 2026)
ABSTRACT Introduction The James Lind Alliance Children's Cancer Priority Setting Partnership identified 23 key research topics, as defined by children, survivors, families, carers, and professionals. Funders have expressed commitment to ensuring all priorities are addressed. The aim of our current project was to map UK‐funded childhood cancer research against the 23 priorities to highlight gaps and inform future funding, policy and research directions. Methods A retrospective grant mapping study. Potential UK funders of childhood cancer research were contacted for details of projects funded January 2020–July 2025. Project abstracts were reviewed to map study aims to one or more of the 23 priorities. Total funding, co‐funders, type of cancer and study design were recorded. Results Of 63 funders contacted, nine declined to participate, eight gave no response and 19 were ineligible as they had not funded relevant work in the study timeframe. Twenty‐seven funders provided data and three had online searchable databases, allowing direct data extraction: 452 studies were mapped. Studies covered all major childhood cancers; 75% were pre‐clinical in design. Total funding awarded was nearly £113 million with 39 co‐funded studies. Priority 1: Developing effective and kinder treatments received most research focus: with 365 studies and £94.2 million funding. Other well‐addressed priorities were Priority 2: Why children develop cancer and can it be prevented : with 73 studies and £16.6 million funding; and Priority 5: Reasons for relapse − 44 studies and £9.6 million. Five priorities received no funding, including Priority 6: Improving hospital experience , which was the top priority identified by children. Conclusion While treatment research is well supported, some areas that matter to children, survivors, families and health professionals are overlooked. Funders and researchers should target underrepresented priorities. Policy makers can use findings to inform delivery of the National Cancer Plan. Patients and families can raise awareness of underfunded areas and influence funding decisions. Patient or Public Contribution This mapping project stemmed from a James Lind Alliance Priority Setting Partnership that had at its core an emphasis on patient participation. Our project team included a survivor of childhood cancer.